EVALUASI KERUSAKAN JALAN LINTAS TIMUR DENGAN MENGGUNAKAN METODE BINA MARGA (Studi Kasus: Jalan Lintas Timur STA 10+000 – 11+000) - Iqbal Abriansyah; Desy Yofianti; Revy Safitri (Jurusan Teknik Sipil Universitas Bangka Belitung, 2022)
Jalan Lintas Timur (the East Highway) serves as an alternative road to divert traffic from the main Pangkalpinang-Sungailiat road. The East Highway is prioritized for industrial or heavy vehicles. The damaged road found in the East Highway’s STA 10+000 to STA 11+000 has reduced the ability to serve the traffic optimally. Therefore, a study on this road damage is imperative. Bina Marga Method is used for the road damage assessment (TP3JK No. 018/T/BNKT/1990). The road is divided into 20 segments, each 50 meters long. Road damage identification is carried out for each segment, untilizing several indicators consisting of level of damage, type of damage, and dimension of damage. The analysis result showed that the damage occurred in East Highway consists of rutting (1.967%), potholes (0.015%), raveling (13.283%), hair crack (0.078%), alligator crack (0.459%), edge crack (0.001%), slippage crack (1.399%), shoving (4.128%), and patching (78.669%). The assessment result of road condition in the East Highway has the average value of 5, with the average number of road damage of 13.6. The Priority Order obtained is 10, indicating that the road has mild damage. Therefore, to overcome the road damage on the East Highway, a routine maintenance program is needed. Key words: East Highway, road damage, bina marga method, road condition, priority order, maintenance program.